INTESTINAL PARASITOSES IN ADULT DOGS AND CATS KEPT IN SHELTERS FOR STRAY ANIMALS - V. B. Yastreb; V. M. Shaytanov (Российский паразитологический журнал)
Objective of research: To reveal the regional specificity of intestinal helminth fauna in stray animals kept in shelters of different regions of Russia. Materials and methods: In 2014-2016 on the basis of a lab of one of the private Moscow vet clinics, 430 fecal samples from dogs and 119 from cats kept in 5 shelters of different regions of Russia were investigated. Fecal samples were delivered to the lab in special plastic containers and examined on the same day by Kalantaryan method using flotation solution of sodium nitrate. Type of eggs, helminth larvae and protozoan oocysts was identified according to their morphological features and size. Samples were submitted to us under condition of confidentiality, therefore we only name the regions where we have investigated the shelters. In Moscow region and in Kirov city, samples from dogs and cats were collected and investigated; in Astrakhan and Novosibirsk - only from dogs and in Krasnodar only from cats. Results and discussion: 7 species of intestinal helminths Toxocara canis, Toxascaris leonina, Trichuris (Trichocephalis) vulpis, Strongyloides sp., Eucoleus sp., family Ancylostomatidae, family Taeniidae and 2 species of protozoa Cystoisospora canis, C. ohioensis were found in dogs; in cats - 4 helminth species Toxocara cati, T. leonina, Trichuris sp., family Ancylostomatidae and 2 species of protozoa C. felis, C. rivolta . Average infestation in dogs with intestinal parasites was 20,4 %, in cats - 46,2 %. The highest infestation in dogs was registered in shelters of Astrakhan (27,7 %) and in Kirov city (24,7 %), little bit lower - in Moscow region (19,3 %), minor infestation - in Novosibirsk (4,9 %). Infestation in cats was almost equal in the regions 38,2-52,2 %. Helminths T. canis were found in dogs from all shelters; in Moscow region and Kirov city, the extensity of invasion was 12,6 and 8,6 %, respectively; in Astrakhan and Novosibirsk - significantly lower 1,4 and 2,4 %. Tr. vulpis dominated in Astrakhan (EI 12,8 %), in Moscow region - only 0,8 %, and in other regions not found. In Kirov city dominated nematodes of the family Ancylostomatidae (13,6 %) that were found sporadically in Moscow region and Novosibirsk. Protozoa Cystoisospora were found in dogs of all shelters (EI from 1,2 to 4,1 %). Helminths T. cati were detected in cats of all shelters (EI from 12,5 to 35,3 %), helminth eggs Trichuris sp. and the family Ancylostomatida e were found in cats only in Krasnodar city. Protozoa of the genus Cystoisospora were found in cats of all shelters (EI from 2,9 % in Moscow region and Krasnodar city, up to 31,2 % in Kirov city).